SPORTS ARE GYMNASTICS IN ACTION SERIES-BE THE MANIFESTATION OF COME. (TECHNICAL SCIENCE RESEARCH IN UZBEKISTAN, 2023)
Man smart, mobility toe‘lish in gymnastics importance is larger. Gymnastic exercises of various toe‘become, sports type all this from exercise to use. They gavin muscles the development of help - giving, to‘g'ri the body shape. This is the reason for also o‘educational institutions, treatment-preventive work in and work out in the field, military service are widely applied.